2008
DOI: 10.1111/j.1365-2672.2008.03912.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of hyphae formation andSIR2expression inCandida albicanstreated with freshAllium sativum(garlic) extract

Abstract: Aims:  The aims of the present study were to determine whether Allium sativum (garlic) extract has any effect on the morphology transformation of Candida albicans, and to investigate whether it could alter the gene expression level of SIR2, a morphogenetic control gene and SAP4, a gene encoding secreted aspartyl proteinase. Methods and Results:  Candida albicans cells were incubated with a range of concentrations of fresh garlic extract, and the morphology was monitored via light microscopy. Garlic extract tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 22 publications
(25 reference statements)
3
34
0
1
Order By: Relevance
“…Our study found that there is a positive correlation between SIR2 expression and true hyphae development. Recently garlic was also shown to be able to suppress hyphae production and also SIR2 expression was shown to be downregulated with increasing concentrations of garlic extract [4].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Our study found that there is a positive correlation between SIR2 expression and true hyphae development. Recently garlic was also shown to be able to suppress hyphae production and also SIR2 expression was shown to be downregulated with increasing concentrations of garlic extract [4].…”
Section: Resultsmentioning
confidence: 98%
“…Therefore the inhibition of filamentation may reduce the pathogenesis of systemic candidiasis. CaSIR2 appears to play a role in phenotypic switching [3], and its expression was recently shown to be suppressed by fresh garlic treatment [4]. Dodecanol has been shown by Hogan et al [5] to be similar to farnesol, a C. albicans quorum-sensing molecule (QSMs), in its ability to inhibit yeast-hyphae transition.…”
mentioning
confidence: 99%
“…Indeed, garlic and some bioactive derivatives reportedly showed antifungal activities in vitro (Low et al, 2008). Hence, the mechanisms of antifungal activity by garlic might be due to direct action against fungi as well as potentiating mucosal immune responses by …”
Section: 3mentioning
confidence: 99%
“…Other signaling compounds (e.g., farnesol [reviewed in reference 62]) and antifungals (e.g., fluconazole [63]) are also toxic at higher levels. Hyphal inhibitors are already being used to treat candidiasis (64, 65), and our finding may lead to enhanced treatment options for C. albicans infections. The mode of action of p -cresol toward C. albicans is unknown.…”
Section: Discussionmentioning
confidence: 84%